Ketercapaian Tugas Perkembangan Remaja SMAN 2 Sungai Penuh Dengan SMAN 1 VII Koto Padang Pariaman - Adril Mahyu; Jarudin Jarudin; Fuaddillah Putra (Jurnal Neo Konseling, 2023)
This research is motivated by the presence of students: they do not comply with the values and rules that exist in school, they cannot get along with friends of different sexes, they are not confident about their physical shape, they are still awkward talking to new friends at school, they wear excessive accessories to school. The aims of the study were 1) to describe the achievement of adolescent developmental tasks at SMAN 2 Sungai Penuh, 2) to describe the achievement of youth developmental tasks at SMAN 1 VII Koto Padang Pariaman, 3) the differences between the achievement of adolescent developmental tasks at SMAN 2 Sungai Penuh and SMAN 1 VII Koto Padang Pariaman. This type of research uses descriptive and comparative quantitative methods. Population 241 people. Sample 110 people. The sampling technique is proportional random sampling. The instrument used was the developmental task inventory (ITP). The data analysis technique uses developmental task analysis (ATP). The results of the study 1) the achievement of adolescent developmental tasks at SMAN 2 Sungai Penuh is at the level of self-awareness, 2) the achievement of adolescent developmental tasks at SMAN 1 VII Koto Padang Pariaman is at the level of self-awareness, 3) the difference between the achievement of adolescent developmental tasks at SMAN 2 Sungai Penuh and SMAN 1 VII Koto Padang Pariaman there is no difference in the achievement of developmental tasks between SMAN 2 Sungai Penuh and SMAN 1 VII Koto Padang Pariaman.